Dual Oral Tissue Adhesive Nanofiber Membranes for pH-Responsive Delivery of Antimicrobial Peptides - Boda, Sunil Kumar (Biomacromolecules, 2020)
Bioadhesive membranes with controllable and reversible underwater adhesion are desirable for several biomedical applications ranging from biosensing, drug/therapeutic delivery, and tissue regeneration. Here, we present dual soft mucosal and hard bone/enamel tissue adhesive nanofiber membranes composed of chitosan and pectin derivatives for pH-controlled delivery of antimicrobial peptides (AMPs) in the oral cavity. Ex vivo testing with porcine esophagus (soft mucosal mimic) indicated a 2-fold increase in the mucoadhesion of chitosan membranes with 0.05 wt % oxidized pectin coating, while the uncoated membranes exhibited 3–4-fold stronger adhesion to hydroxyapatite discs (enamel/hard bone mimic) compared to the coated membranes. The former is attributed to a synergistic interaction of surface nanofiber topography, intermolecular hydrogen bonding, and aldehyde–amine chemistry between surface polar groups and mucosal proteins, while the latter may arise from electrostatic interactions between cationic amines (─NH(3)(+)) in chitosan and anionic phosphates (─PO(4)(3─)) in hydroxyapatite. Further, the dual hard–soft oral tissue adhesive nanofiber membranes loaded with cationic amphipathic AMPs (D-GL13K and IDR-1018) elicited pH-responsive AMP delivery and antimicrobial action comparable to chlorhexidine (CHX) against oral streptococci. Concurrently, the AMP loaded membranes were cytocompatible to both soft epithelial tissue-derived human oral keratinocytes and hard calvarial murine pre-osteoblast cells. We envision these membranes to function as adhesive gingival grafts and guided bone regeneration (GBR) membranes at the hard–soft tissue interface while simultaneously protecting against oral infections.